: PELATIHAN TEKNIK DASAR TOLAK PELURU PADA SISWA SMP NEGERI SATU ATAP DESA JAYA BHAKTI KECAMATAN ENOK KABUPATEN INDRAGIRI HILIR - Rahmad yulmiando; Prima Antoni; Hamzah Hamzah; Devit Wilastra; Dahrial Dahrial (KARYA ABDI, 2020)
This type of research is correlational. The objective of this research is to determine the extent of "The Relationship between Arm Muscle Strength and Bullet Resistance Ability in Students of OneRoof Junior High School in Jaya Bhakti Village, Enok District, Indragiri Hilir Regency. The populationin this study were all students of One Roof State Junior High School in Jaya Bhakti Village, EnokDistrict, Indragiri Hilir Regency, which numbered 10 VIII grade students. Samples were taken using theTotal technique and the results of the training of basic techniques of shot repelling are success - theimplementation of this community service activity can be seen from the results of the evaluation duringthe implementation of the activity, namely: The success - the implementation of this community serviceactivity can be seen from the results of the evaluation throughout the implementation of the activity,namely: Persistence and involvement of the participants training in involving themselves in theimplementation of this training activity, the participants or students have knowledge in the field of sports,especially bullet shooting. There is an increase in the ability to understand both theoretically andpractically the sport of shot put.